Assessing Socio-cultural Practices and Economic Situations of Gurung Community in Phungling Municipality-8, Taplejung District, Nepal (Pathibhara Journal of Multidisciplinary Research, 2026)
This study assesses socio-cultural practices and economic situation of Gurung community in Phungling Municipality Ward No. 8, Taplejung district, Nepal. The objectives were to examine social demographic, socio-cultural practices as well as economic situations of the respondents residing in the study area. The study used descriptive research design and case study method for assessing daily life and livelihoods of Gurung community within its real-life context. Required numerical data were collected from 40 married youths (aged 20-60 years) selected randomly. Likewise, required narratives information were generated from nine articulating participants selected purposively. Data was collected through self-administered household surveys questionnaires and in-depth interview guideline. The findings reveal that the community maintains rich cultural traditions including life-cycle rituals (Nawaran, Pasni, Chhaewar, Gunyo-Choli, marriage, death ceremonies) where astrologers determine auspicious dates and the maternal uncle plays a significant role. However, traditional performing arts like Ghatu dance are declining due to fading oral traditions and geographic displacement from the Gurung heartland. Economically, the community exhibits diversified livelihoods with agriculture (40%) and foreign employment (35%) as primary occupations, followed by government service (20%) and business (5%). All households practice livestock rearing, with many engaging in seasonal migration for grazing. Income distribution reveals economic differentiation, with foreign employment creating both opportunities and disparities. The study concludes that the Gurung community in Taplejung crosses between preserving cultural identity and adapting to modern socio-economic realities, facing challenges of cultural erosion, limited higher education access, and economic inequality. Policy implications include cultural preservation programs, access and continuing higher educational and improving economic situation through agro-tourism based livelihood strategies.